2003
DOI: 10.1038/sj.hdy.6800253
|View full text |Cite
|
Sign up to set email alerts
|

The likely fate of hybrids of Bactrocera tryoni and Bactrocera neohumeralis

Abstract: Bactrocera tryoni (Froggatt) and B. neohumeralis (Hardy) (Diptera: Tephritidae) are sympatric species which hybridise readily in the laboratory yet remain distinct in the field. B. tryoni mates only at dusk and B. neohumeralis mates only during the day, but hybrids can mate at both times. We investigated the inheritance of mating time in successively backcrossed hybrid stocks to establish whether mating with either species is more likely. The progeny of all backcrosses to B. tryoni mated only at dusk. The majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Certainly, if, as it appears, the species are largely maintaining their reproductive isolation in nature, a strong directional bias in gene flow may be the process supporting this. However, observations of laboratory-bred hybrids suggest an alternative mechanism that could minimise genetic exchange between the species: hybrids with yellower calli (tryoni-like) tend to mate at dusk with B. tryoni, while hybrids with browner calli (neohumeralis-like) tend to mate during the day with B. neohumeralis (Pike et al 2003). Wolda (1967b) reported that artificial selection of B. neohumeralis was not sufficient to produce flies with true yellow calli (as seen in B. tryoni, hybrids, and intermediates).…”
Section: Discussionmentioning
confidence: 96%
“…Certainly, if, as it appears, the species are largely maintaining their reproductive isolation in nature, a strong directional bias in gene flow may be the process supporting this. However, observations of laboratory-bred hybrids suggest an alternative mechanism that could minimise genetic exchange between the species: hybrids with yellower calli (tryoni-like) tend to mate at dusk with B. tryoni, while hybrids with browner calli (neohumeralis-like) tend to mate during the day with B. neohumeralis (Pike et al 2003). Wolda (1967b) reported that artificial selection of B. neohumeralis was not sufficient to produce flies with true yellow calli (as seen in B. tryoni, hybrids, and intermediates).…”
Section: Discussionmentioning
confidence: 96%
“…The highly polyphagous species of the FAR complex show largely overlapping distributional areas and host spectra . However, the elaborate species-specific mating behaviour of fruit flies (Quilici et al, 2002;Pike et al, 2003) is supposed to prevent inter-specific hybridisation under field conditions. Interspecific hybrids of the three FAR morphospecies have hitherto not been reported from natural populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although this hypothesis was subsequently discounted (Gibbs, 1968;Birch and Vogt, 1970), more recent applications of molecular genetic markers have supported the original conclusion that B. neohumeralis genes have introgressed into B. tryoni (Morrow et al, 2000). Pike et al (2003) found that the cause of the asymmetry in gene flow between these two species-from B. neohumeralis into B. tryoni-was a difference in mating period. In conclusion, the hypothesis that introgression can greatly expand a pest species' niche (Lewontin and Birch, 1966) is supported by findings from the Bactrocera complex.…”
Section: Cowania/purshiamentioning
confidence: 90%